THU0194 Role of Platelets in the Pathogenesis of Osteoarthritis and Biological Effects of Hyaluronic Acid: in Vivo and in Vitro Study. (10th June 2014) - Alunno, A.; Petito, E.; Mirabelli, G.; Falcinelli, E.; Luccioli, F.; Momi, S.; Bartoloni, E.; Santoboni, G.; Bistoni, O.; Caterbi, S.; Gresele, P.; Gerli, R.
Abstract : Background: Although osteoarthritis (OA) is a degenerative joint disorder, it has been demonstrated that inflammation takes part in the development and progression of this condition. Matrix metalloproteinases (MMPs), including MMP-2, are involved in the cartilage breakdown observed in OA. Platelets (PLTs) are involved in different inflammatory conditions, including rheumatoid arthritis, contain and release several MMPs, including MMP-2, and enhance MMPs expression by other cell types. However, their role in OA has not been investigated yet. Hyaluronic acid (HA) is a normal component of extracellular matrix and synovial fluid (SF). Intra-articular (IA) administration of HA in OA is widely employed in clinical practice with good clinical efficacy. Objectives: Aims of our study were to investigate the role of platelets and MMP-2 in the pathogenesis of OA, to test the biologic activity of IA-HA in OA patients and to analyze the effects of HA on the interaction between platelets and synoviocytes in vitro. Methods: Thirty-eight patients with knee OA were screened and twenty-four patients were included in the study. Systemic therapy with non-steroidal anti-inflammatory drugs or corticosteroids and previous IA corticosteroid treatment represented exclusion criteria. Five injections of IA sodium hyaluronate (500-730 KDa) were administrated weekly. SF samples were collected prior to the first (T0) and at the last (T1) injection. Total cell and PLT count, platelet-leukocyte aggregates (PLT activation marker) and MMP-2 levels were measured in SF. For clinical assessment at T0, T1 and 3 months after the last injection (T3) the Western Ontario and Mc Masters University (WOMAC) scale and VAS for knee pain were employed. Fibroblast-like synoviocytes (FLS) were isolated from untreated OA-SF and cultured with PLTs in presence or absence of HA at different concentrations for 24 hours. Platelet P-selectin was measured by flow-cytometry and MMP-2 in culture supernatants was quantified by zymography. Results: Total cell count in SF was significantly reduced after IA-HA (p<0.05). PLT count, platelet-leukocyte aggregates and MMP-2 concentration were significantly decreased at T1 (all p<0.05). WOMAC scale and pain VAS were reduced at T1 (p<0.0001) and this decrease was maintained at T3. MMP-2 production by FLS was significantly higher in the presence of PLTs and this increase was significantly reduced by co-incubation with HA. P-selectin expression, marker of PLT activation, was significantly higher in PLTs cultured with FLS and P-selectin blockade reduced MMP-2 release in culture supernatants. Conclusions: Our results show that PLTs, in addition to other inflammatory cells, participate in the pathogenesis of OA by the induction of MMP-2 release by FLS possibly via P-selectin, thus contributing to cartilage breakdown. Treatment with HA decreases count and activation of PLT and levels of MMP-2 in the SF. PLT and synoviocytes interaction leads to platelet activation and MMP-2 release enhancement. Hence, PLTs may represent a new therapeutic target in OA. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4585